2017
DOI: 10.14207/ejsd.2017.v6n3p439
|View full text |Cite
|
Sign up to set email alerts
|

Materiality Analysis in Sustainability Reporting: A Method for Making It Work in Practice

Abstract: Sustainability reporting is the practice of measuring, disclosing, and being accountable to internal and external stakeholders for the company's ability to achieve sustainable development goals (SDGs) and manage impacts on society. According to the Global Reporting Initiative (GRI) G4 guidelines, the purpose of materiality analysis in sustainability reporting is to determine those economic, environmental and social issues that are the most significant to company and its stakeholders. A key challenge is to ensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 19 publications
0
44
1
4
Order By: Relevance
“…Nevertheless, a review of the literature revealed that materiality analysis presents critical issues that limit its practical use in companies (Pérez-López et al, 2015;Calabrese et al, 2017). Materiality analysis is in fact a highly subjective process that requires mediating among potential conflicts, and dealing with uncertainty and consistency of judgments across a wide range of issues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, a review of the literature revealed that materiality analysis presents critical issues that limit its practical use in companies (Pérez-López et al, 2015;Calabrese et al, 2017). Materiality analysis is in fact a highly subjective process that requires mediating among potential conflicts, and dealing with uncertainty and consistency of judgments across a wide range of issues.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, materiality analysis presents criticalities that limit its practical use in companies (Calabrese, Costa, Ghiron, & Menichini, 2017). The process of assessing materiality requires companies to consider the strategic value of the opportunities and risks related to the various aspects of sustainability.…”
Section: Materiality In Sustainability Reportingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of traditional financial reporting, the concept of materiality is shaped by both quantitative and qualitative aspects, all of them defined and written down in standards set by international organizations, imposed by governments, and used as a basic element of market-based investment decision-making [27,28]. For nonfinancial information, the narrative is very different, as this information cannot be directly and clearly valued in a market setting [29].…”
Section: Materiality and Stakeholder Inclusionmentioning
confidence: 99%
“…A sustainability report gives information about economic, environmental, social and governance performance. Other words, sustainability reporting is the practice of measuring, disclosing, and being accountable to internal and external stakeholders for the company's ability to achieve sustainable development goals and manage impacts on society (Calabrese et. al.…”
Section: Review Of the Literaturementioning
confidence: 99%